Main features of family functioning in families with pediatric asthma of varying severity - Y. Yu. Galitsyna (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
This research is focused on studying the types of education, parental attitudes and characteristics of defending strategies in families with pediatric asthma. Families with pediatric asthma have discovered a rigid system of family functioning and an existence of strict familiarly rules and roles. Based on the study results, where the factor analysis was applied, three groups of families with pediatric asthma were defined depending on to what degree the family functioning is violated. The correlation has been found between the characteristics of family functioning and severity of pediatric asthma.